Indirect evidence of an early mating advantage in wild cooperatively breeding male banded mongooses - Graham Birch; Michael A. Cant; Hazel J. Nichols; Magali Meniri; Robert Businge; Francis Mwanguhya; Jonathan D. Blount (Scientific Reports)
Abstract Promiscuous females reduce male reproductive control. Males can attempt to monopolise access to these females, but distractions and sneaky rivals mean extra copulations cannot always be blocked. By mating first, males can obtain a headstart in sperm competition, but this may be negated by sperm storage and cryptic female choice mechanisms. We carry out an indirect rare test of an early mating advantage in a population of free-living wild animals. Using Bayesian GLMM analysis of a long-term life history database spanning 17 years, we show that banded mongoose males who interacted with females in earlier days of oestrus had a higher chance of siring their offspring compared with later rivals. An early mating advantage would intensify initial male-male competition and hence selection for male choice, as any initial mistake identifying preferred mating partners could see paternity lost to rivals.